2013
DOI: 10.1097/rlu.0b013e318292a73b
|View full text |Cite
|
Sign up to set email alerts
|

Unsuspected Uterine Metastasis of Breast Carcinoma Diagnosed by 18F-FDG PET/CT

Abstract: A 50-year-old woman with a history of bilateral lobular carcinoma of the breast in 1995 and 2001 was treated with mastectomy, axillary lymphadenectomy, chemotherapy, and hormone therapy which achieved a complete response. In 2009, the patient developed a progressive elevation of tumor markers. A CT scan was performed showing no suspicious malignant lesions. She was referred for (18)F-FDG PET/CT and the images revealed highly increased tracer uptake in the uterus suggestive of malignancy. The patient underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This case indicates uterine lymphoma should be included in the differential diagnosis of abnormal uterine FDG accumulation along with physiological endometrial uptake, 11 postpartum uterus, 12 adenomyosis, 13,14 endometrial hyperplasia, 14 leiomyoma, 14,15,16 cervical cancer, 14,17 endometrial cancer, 14,18 choriocarcinoma, 19 uterine sarcoma, 14,16,20 and uterine metastasis. 14,21 …”
Section: Discussionmentioning
confidence: 99%
“…This case indicates uterine lymphoma should be included in the differential diagnosis of abnormal uterine FDG accumulation along with physiological endometrial uptake, 11 postpartum uterus, 12 adenomyosis, 13,14 endometrial hyperplasia, 14 leiomyoma, 14,15,16 cervical cancer, 14,17 endometrial cancer, 14,18 choriocarcinoma, 19 uterine sarcoma, 14,16,20 and uterine metastasis. 14,21 …”
Section: Discussionmentioning
confidence: 99%
“…However, the increased uptake in a postmenopausal woman should raise the suspicion of malignancy and initiate further workup. In this study, the case reported by Muñoz-Iglesias et al [14] had no uterine symptoms, but the progressive elevation of tumor markers after 6 years of management of bilateral lobular carcinoma of the breast led to PET-CT and the discovery of uterine metastasis. In the cases reported by Thouvenot et al [34], D'souza et al [6], and Danolić et al [45] , PET-CT revealed widespread metastatic lesions.…”
Section: Discussionmentioning
confidence: 55%
“…İşçi et al, [13] 2011 47 ILC + -YES (letrozole) During the follow-up CT Surgery + chemotherapy Dirican et al, [14] 2012 51 IDC -+ YES (tamoxifen) During the follow-up CT + tumor marker Surgery + chemotherapy van et al, [15] 2012 70 IDC NA NA YES (tamoxifen) During the follow-up CT Surgery Munoz-Iglesias et al, [16] 2013 50 ILC NA NA YES (NA) During the follow-up Tumor marker + PET/CT Surgery Proenca et al, [17] The female reproductive system is rarely affected by metastasis. The most common site of metastasis is the ovary, followed by the vagina (75.8% and 13.4%).…”
Section: Mri Chemotherapy + Radiotherapymentioning
confidence: 99%